Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Air Minum dalam Kemasan (AMDK) Merek Rotat Mineral Pada PT. Pintar Sumber Mineral: (Studi Kasus Pada Konsumen Kecamatan Nita Kabupaten Sikka) - Paskalis Baylon Cawa; Antonius Philipus Kurniawan; Nunsio H. Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aimed to (1) understand the overview of Purchase Decisions, Product Quality, and Promotion; (2) analyze the influence of Product Quality and Promotion on Purchase Decisions both partially and simultaneously. The population in this research consisted of consumers of Packaged Drinking Water (PDW) of Rotat Mineral brand residing in Nita Sub-district, Sikka Regency. Due to the unlimited population, a sample of 100 people was taken. Data were collected through questionnaires and analyzed using descriptive inferential methods, namely multiple linear regression. Hypothesis testing was conducted using the F-test and t-test. The descriptive analysis showed that the variables of Product Quality, Promotion, and Purchase Decision were good. The t-test statistical results indicated that partially, Product Quality and Promotion variables had a positive and significant influence on Purchase Decisions. The F-test statistical results showed that all independent variables simultaneously significantly influenced Purchase Decisions. The determination analysis results showed the contribution of Product Quality and Promotion variables to the Purchase Decision of Packaged Drinking Water (PDW) brand Rotat Mineral at PT. Pintar Sumber Mineral (Case Study on Consumers in Nita Sub-district, Sikka Regency) was 26.9%, while other factors outsidc thc rescarch variables influcnccd thc rcmaining 73.1%.